EFFECTS OF A DIABETES SELF-MANAGEMENT EDUCATION AND SUPPORT PROGRAM ON HEALTH BEHAVIORS AND HbA1c LEVELS AMONG PEOPLE WITH UNCONTROLLED TYPE 2 DIABETES - Udompai, Pattanakron; Mangalakhiri, Nucharat; Tumdee, Decha (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This quasi-experimental study aimed to compare the average health behavior scores and the hemoglobin A1c (HbA1c) among patients with poorly controlled type 2 diabetes before and after using the program of the experimental group and between the experimental group and the comparison group. Participants were patients receiving care at a Sub-district Health Promoting Hospital in Mueang District, Udon Thani Province. Sixty participants were randomly assigned to either an experimental group (n = 30) or a control group (n = 30) a combination of simple and systematic random sampling. The experimental group underwent a 12-week Diabetes Self-Management Education and Support (DSMES) intervention, validated by 3 experts, while the control group received standard care. The data collection instruments utilized in this study included a questionnaire assessing blood glucose management behaviors and a HbA1c record form. The questionnaire assessing blood glucose management behaviors has undergone content validity verification and demonstrated reliability with a Cronbach's alpha coefficient of .76. Data was analyzed using descriptive statistics, independent t-tests, paired t-tests and Chi-square test. The results indicated that after the intervention, the experimental group demonstrated statistically significant improvements in dietary practices, physical activity, stress management, and medication adherence compared to the control group (p < .05). Moreover, the experimental group exhibited a significantly greater reduction in HbA1c levels than the control group (p < .05). These results support the use of the DSMES program as an effective intervention to enhance self-care behaviors and glycemic control in patients with uncontrolled type 2 diabetes and highlight the need for ongoing monitoring to maintain long-term blood sugar management.